Laryngeal paraganglioma - Freitas, Luís (2013)
Paragangliomas are neuroendocrine system tumors, with a low incidence in the head and neck. In the larynx, there are three distinct locations, the majority arise in the supraglottic larynx. They are considered benign tumors without metastatic capacity; the differential diagnosis with other neuroendocrine lesions is necessary, given the different therapeutic approaches. Surgical excision is considered the treatment of choice. Since the introduction of Laser CO2 surgery, some cases have been reported, but the degree of success is not standard. The authors present a case of supraglottic laryngeal paraganglioma in a 71 years old patient, that underwent a microlaryngoscopy with Laser CO2 excision. This therapeutic approach allowed tumor excision without tracheostomy, with follow up to three years without signs of local recurrence. Histology, immunohistochemistry and images obtained by contact endoscopy are documented and analyzed.